معدل انتشار الأضداد المصلية لفيروس الحماق – داء المنطقة في مجموعات عمرية مختلفة في محافظة اللاذقية - كراوي, مازن; الخياط, محمد; علي, ديما (Latakia University Journal -Medical Sciences Series, 2019)
أجريت الدراسة في محافظة اللاذقية على 261 عينة موزعة على أربع فئات عمرية: (6-0) سنوات, (12-6) سنة, (18-12) سنة, (30-12) سنة, وقد جمعت هذه العينات بصورة عشوائية من مرضى مشفى الأسد الجامعي, مراجعي العيادات الخارجية وطلاب مدارس في محافظة اللاذقة بعد استبعاد حالات: المرض الحاد, ارتفاع الحرارة > 38.5o, المعالجة الحديثة بالغلوبولينات المناعية أو بكابتات المناعة, حالات نقص المناعة, عينات الدم المنحلة, ثم تمت معايرة أضداد فيروس الحماق - داء المنطقة VZV باستخدام طريقة المقايسة المناعية الأنزيمية ELISA. أظهرت الدراسة زيادة في معدل الأضداد المصلية lgG لفيروس الحماق – داء المنطقة مع العمر عند الذكور والإناث حيث كان معدل الانتشار المصلي 21.06% في المجموعة العمرية (0-6) سنوات, 44.18% في المجموعة العمرية (6-12) سنة, 77.01% في المجموعة العمرية (12-18) سنة, 86.5% في المجموعة العمرية (18-30) سنة. تظهر النتائج وجود معدل مرتفع لانتشار التعرض للعدوى في محافظة اللاذقية ومتزايد مع تقدم العمر مما يشير لفائدة إدخال اللقاح في برنامج التلقيح الوطني في سورية للحد مستقبلاً من انتشار العدوى وعواقبها. This study was carried out in Lattakia on 261 samples distributed into four age groups: (0-6) years, (6-12) years, (12-18) years, and (18-30) years. These samples were randomly collected from patients (outpatients and school students) admitted to Al-Asad University Hospital in lattakia, ruling out the following cases: acute illness, fever >38.5, recent administration of immunoglobulins, blood products or immunosuppressive therapy, immunosuppressive conditions, and hemolysed blood samples. Then we titrated the antibodies of Varicella-Zoster virus VZV, using enzyme-linked immunoabsorbent assay (ElISA). This study revealed an increase in the ratio of serum antibodies lgG of Varicella-Zoster virus with advancement in age for males and females, whereas seroprevalence was 21.06% in the (0-6) age group, 44.18% in the (6-12) age group, 77.01% in the (12-18) age group, 86.5% in the (18-30) age group. The results showed an increase in infection spreading in Lattakia; this indicated the efficacy of using the vaccine in the national vaccination program in Syria to reduce the spread of the disease and its consequences in the future.